The Ubiquitous Nature of Style in the Translation of Literary and Non-literary Texts - Prof. Basil Hatim (My University, 2011)
In this workshop, the notion of style will be introduced and is sufficiently broadened to include values relating not only to literariness (i.e. style in the traditional sense) but also and more significantly to all aspects of creativity in the use of language. Thus, a Shakespearean sonnet and the instructions on a medicine bottle are both worthy objects of stylistic investigation. It will be further suggested that the style of any text is not as elusive as was once thought. Rather, it is a fact of texts in context manifested by a diverse range of ‘communicative clues’, some explicit, some implicit. In the process of translating, these source text clues and the features involved must be assessed for ‘relevance’ and, if ‘relevance’ is established, must be preserved in the target end-product by an equally potent set of ‘communicative clues’.

In this workshop, the notion of style will be introduced and is sufficiently broadened to include values relating not only to literariness (i.e. style in the traditional sense) but also and more significantly to all aspects of creativity in the use of language. Thus, a Shakespearean sonnet and the instructions on a medicine bottle are both worthy objects of stylistic investigation. It will be further suggested that the style of any text is not as elusive as was once thought. Rather, it is a fact of texts in context manifested by a diverse range of ‘communicative clues’, some explicit, some implicit. In the process of translating, these source text clues and the features involved must be assessed for ‘relevance’ and, if ‘relevance’ is established, must be preserved in the target end-product by an equally potent set of ‘communicative clues’.
The Ubiquitous Nature of Style in the Translation of Literary and Non-literary Texts